Formal social support and quality of life of caregivers with autistic children: a large-scale nationwide survey in China - Ran, Qingqing; Tu, Liangzhi; Wu, Yinghui; Zhang, Shunming; Zhang, Erliang; Li, Huilun; Su, Ya; Xiang, Mi (Frontiers in Public Health, 2023)
Introduction Caregivers of children with autism spectrum disorder (ASD) were reported poor quality of life (QOL). Formal social support might improve the QOL of caregivers, however, limited research to date has focused on this association in China and formal social support for this group is conspicuously lacking. The study was aim to understand the QOL in male and female caregivers with ASD children in China and to explore the relationship between QOL and formal social support for caregivers with children with ASD through a large-scale nationwide survey. Methods An online questionnaire was used to conduct a cross-sectional study with a sample of 6,120 caregivers of children with ASD. Relationship between Quality of Life and several potential predictors is measured and analyzed. Quality of life were measured by Medical Study Short-Form Health Survey version 2 (Chinese version). Multivariate logistic regression analysis was used to analyze the factors affecting caregivers' QOL. Results The results revealed that the QOL of caregivers of autistic children in China was poor especially male caregivers. Social support was a positive predictor. More importantly, formal social support from rehabilitation institutions can improve caregivers' physical QOL. Caregivers' satisfaction with the rehabilitation institutions affecting their physical and mental QOL. Conclusion The formal social support provided by rehabilitation institutions plays a positive role in improving the quality of life of caregivers.